The Dynamic of the Present Day in the Lexicon Mirror - Długosz , Natalia (Poznańskie Studia Slawistyczne, 2020)
This review is a short presentation and an analysis of the book Динамика и иновации в лексикалната система на българския език, published in 2019 in Plovdiv. The book consists of nine parts, each dealing with a different type of linguistic processes (archaisation, terminologisation and determinologisation, lexicalisation, univerbation, neologisation, internationalisation) occurring in the lexical system of contemporary Bulgarian. Linguistic changes in the lexical sphere are presented in the context of dynamic changes in the methods of communication, determined by non-linguistic reality. The monograph deals with new vocabulary, from the end of the 20th century to the present day. It contains a synthetic review of certain positions within the scope of the discussed linguistic processes. An effort was also made to organise the terminology used in Bulgarian linguistic studies. The advantage of the monograph resides in the original propositions for the interpretation of individual phenomena and the author’s own propositions for definitions. What makes the publication particularly interesting is the presentation of an experimental study in the field of examining language competence and language memory of those Bulgarian language users who represent the generation of today’s students.